Public-Private Partnerships for Urban Water Utilities : A Review of Experiences in Developing Countries - Marin, Philippe (World Bank, 2012)
This study provides objective information and analysis on the performance of public-private partnerships (PPP) projects in urban water supply and sanitation in developing countries. It reviews the spread of urban water PPP projects during the past 15 years, and assesses whether and how they have helped to improve services and expand access for the populations concerned. The study uses a structured framework to assess the performance of more than 65 large water PPP projects that have been in place for at least five years (three years in the case of management contracts) and that provide services to a combined population of almost 100 million. By population size, this sample represents close to 80 percent of the water PPP projects that were awarded before 2003 and have been active for at least three years. The analysis focuses on the actual impact of these projects for the concerned populations, that is, the net improvements achieved under these partnerships. Chapter two summarizes the historical development of water PPPs in developing countries, reviewing the current state of the market, the rate of contract cancellations, and the evolution of the industry. Chapter three reviews the performance of PPP projects in terms of access, service quality, operational efficiency, and tariffs. Chapter four draws conclusions and lessons on how to make public-private partnership a more viable and sustainable option for improving water supply and sanitation (WSS) services in the developing world.